Who and how produces the future (Alexander Fedorov’s new philosophy of common cause) - Grigorii L. Tulchinskii (Слово.ру: балтийский акцент)
The article presents a reflection on Alexander Fedorov's project aimed at analysing the future and the model of production. This model facilitates the correlation of factors related to subjectivity and sociality within the process of future production. Notably, the work emphasizes Alexander Fedorov's assertion regarding the pivotal role of children and childhood and the typology of actors involved in this process. The proposed concept and model establish a fertile ground for further interdisciplinary research. From the perspective of social semiotics and pragmasemantics, shaping the future emerges as a form of meaning-making and institutionalization, unfolding through a series of interfaces that enable interaction across socio-cultural practice contexts. In this framework, subjectivity is identified as a crucial interface for such interactions. Moreover, a comparative analysis of natural and artificial intelligence underscores the complex potential inherent in this research problem. While human beings possess advantages stemming from bodily experience, sexual dimorphism, and other forms of vitality over artificial intelligence, the future is largely grounded in this vitality, exemplified by the essence of childhood. Consequently, the question of management possibilities and the ethical dimensions of future production, as well as the balance between permissible and impermissible means employed, becomes particularly salient.